Enhancement of a Heroin Vaccine Through Hapten Deuteration - Belz, Tyson F. (J Am Chem Soc, 2020)
The United States is in the midst of an unprecedented epidemic of opioid substance use disorder and while pharmacotherapies including opioid agonists and antagonists have shown success, they can be inadequate and frequently result in high recidivism. With these challenges facing opioid use disorder treatments immunopharmacotherapy is being explored as an alternative therapy option and is based upon antibody-opioid sequestering to block brain entry. Development of a heroin vaccine has become a major research focal point, however, producing an efficient vaccine against heroin has been particularly challenging because of the need to generate not only a potent immune response but one against heroin and its multiple psychoactive molecules. In this study, we explored the consequence of regioselective deuteration of a heroin-hapten and its impact upon the immune response against heroin and its psychoactive metabolites. Deuterium (H(dAc)) and cognate protium heroin (H(Ac)) haptens were compared head to head in an inclusive vaccine study. Strikingly the H(dAc) vaccine granted greater efficacy in blunting heroin analgesia in murine behavioral models compared to the H(Ac) vaccine. Binding studies confirmed that the H(dAc) vaccine elicited both greater quantities as well as equivalent or higher affinity antibodies towards heroin and 6-AM. Blood-brain bio-distribution experiments corroborated these affinity tests. These findings suggest that regioselective hapten deuteration could be useful for the resurrection of previous drug of abuse vaccines that have met limited success in the past.